2011
DOI: 10.1007/s13361-010-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Capture and -Transfer Dissociation of Peptides Tagged with Tunable Fixed-Charge Groups: Structures and Dissociation Energetics

Abstract: Pyridiniummethylcarbonyl moieties that were previously designed on the basis of electronic structure analysis are now utilized as fixed-charge tags with tunable electronic properties to be used for N-terminal peptide derivatization and sequencing by electron-transfer dissociation. Dipeptides AK and KA were derivatized at the peptide N-terminus with 4-dimethylaminopyridinium-N-acetyl (DMAP-ac) and pyridinium-N-acetyl (pyrid-ac) tags of increasing intrinsic recombination energies. Upon the capture of a free elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…We speculate that the pyridine functional group sequesters the transferred electron and produces uninformative side-chain fragmentation products rather than backbone cleavages, as has been observed for ETD and ECD of various peptides having heterocyclic aromatic groups [8, 5557]. Interestingly, Turecek has found that a pyridinium group, attached to a peptide’s N-terminus, served as a good functional group for improving ETD [58, 59]. While similar in structure, the pyridinium differs from the pyridine employed here in that the nitrogen atom resides on the opposite side of the aromatic ring and it is quaternary, rather than tertiary.…”
Section: Resultsmentioning
confidence: 93%
“…We speculate that the pyridine functional group sequesters the transferred electron and produces uninformative side-chain fragmentation products rather than backbone cleavages, as has been observed for ETD and ECD of various peptides having heterocyclic aromatic groups [8, 5557]. Interestingly, Turecek has found that a pyridinium group, attached to a peptide’s N-terminus, served as a good functional group for improving ETD [58, 59]. While similar in structure, the pyridinium differs from the pyridine employed here in that the nitrogen atom resides on the opposite side of the aromatic ring and it is quaternary, rather than tertiary.…”
Section: Resultsmentioning
confidence: 93%
“…Generally, the peptides are protonated, although use of metal cations or synthetic charge tags can provide additional charge sites by chemical modifications. [11][12][13] An additional increase in peptide charge, or supercharging, is achieved by modifying solvent composition and ion source parameters, as discussed elsewhere. 14 For simplicity, here only protonation as a means of peptide or protein charging is considered.…”
Section: Analytical Aspects Of Ecd/etd Mass Spectrometrymentioning
confidence: 99%
“…(1) Identification of the precursor ion and charge-reduced species. Since the m/z value of the precursor ion is known, use the formula q = n À 1, where q is the charge state and n is the number of isotopic peaks per 1 m/z unit, to determine the charge state of the precursor ion (since 12 C and 13 C isotopes differ by B1 Da, Table 1). Knowing the m/z value and the charge state of the precursor ion, it is possible to derive the m/z value of the charge-reduced species.…”
Section: Protocol For Peptide Sequencing By Exd Ms/msmentioning
confidence: 99%
“…The N,N-dimethylaminopyridyl-1-methylcarboxamido (DMAP) group has recently been shown to substantially improve ETD sequence coverage of small peptides [52]. We therefore focused on studying a broader series of penta-, nona-, and decapeptides tagged with DMAP at the Ntermini.…”
Section: Fixed-charge Pyridinium Tagsmentioning
confidence: 99%